Heavy on plans, light on delivery: The structural failures of Ethiopia's nutrition policies - Zerfu, Taddese Alemu (Wiley, 2025)
Ethiopia's development ambitions rest on the foundation of a healthy population, yet its nutrition sector remains stalled despite decades of planning and investment. Nearly 38% of children under five are stunted, and food insecurity continues to affect millions. Landmark initiatives like the National Food and Nutrition Policy and the Seqota Declaration demonstrate strong political will—but implementation and scale-up falters due to entrenched structural failures. At the core of this breakdown is an overstretched and under-resourced frontline workforce. Health Extension Workers, while committed, are burdened with wide-ranging responsibilities, and lack the specialized training needed for effective nutrition service delivery. As a result, national strategies often collapse at the community level, where change is most urgently needed. This is further compounded by fragmented coordination. Despite the multisectoral nature of malnutrition—spanning health, agriculture, education, and social protection—ministries and partners frequently work in silos, sending conflicting messages to the same households. Meanwhile, valuable research and data remain disconnected from policy and program implementation, limiting the system's responsiveness and accountability. The path forward requires more than incremental fixes. Ethiopia needs specialized community nutrition workers to bridge the last-mile gap, a high-level coordination mechanism to align sectoral actions, and agile policies grounded in real-time evidence. Without these structural reforms, the burden of malnutrition will continue to erode the country's human capital and economic potential. This is not just a health crisis—it is a critical bottleneck to national progress. The time for structural transformation is now.